Ketika Ijazah Menentukan Demokrasi : Persepsi Masyarakat Terhadap PSU Pilkada Pesawaran - Titan Cicilia; Esti Angelita; Feby Fiola Ayu; Zahra Nur Farida; Asshifa Shalihah; Abdul Halim (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The Constitutional Court’s decision to mandate a revote (Pemungutan Suara Ulang, PSU) in the 2024 Pesawaran local election due to issues regarding the authenticity of one candidate's diploma has sparked significant democratic discourse. This article aims to explore the perceptions of the public and election organizers regarding the PSU and the role of educational credentials as a determining factor in democratic processes. This study adopts a qualitative case study approach through direct interviews with KPPS (Polling Station Working Committee) members and residents of Pesawaran. Findings reveal that the public generally accepted the PSU as a fair solution (MA, interview, 2025), though some expressed frustration over the political process described as "full of drama." Meanwhile, KPPS members stated that preparations for the PSU were adequate, with logistics well-distributed and personnel properly retrained, though maintaining voter turnout remained a challenge (RD, interview, 2025). Administratively, the diploma is perceived as both a legal and moral requirement for candidacy, aligning with Khairunnisa (2022), who argued that administrative completeness is essential for the ethical and lawful nomination of regional leaders. This case highlights persistent challenges in local democratic governance, particularly in maintaining public trust when a candidate’s formal qualifications are contested. Transparent and rigorous candidate verification processes are crucial to preventing political uncertainty and preserving electoral integrity.